Tracking career performance of successful triathletes - Malcata, R. M.; Hopkins, W. G.; Pearson, S. N. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Tracking athletes` performances over time is important but problematic for sports with large environmental effects. Here we have developed career performance trajectories for elite triathletes, investigating changes in swim, cycle, run stages, and total performance times while accounting for environmental and other external factors.